DEVELOPMENT OF GOOGLE SITES-BASED INTERACTIVE MEDIA ON FOLKTALE MATERIAL FOR FIFTH-GRADE STUDENTS AT SD NEGERI TANGGUNGAN - Sundari Wati; Adi Bandono; Achmad Noor Fatirul (Universitas Bina Bangsa Getsempena, 2025)
A goal of this research is to set up learning media suitable for folktales like Google Sites did. the fifth grader students at SDN Tanggungan will be better at telling stories after reading this material. In this study, we attempt to solve the lack of digital media that Merdeka Curriculum-Framework speaking poses to students' skills and endeavours. This paper reports on a study using expert validation as well as individual (3 students), small-group (6 students) and large-group (25 students) trials. The ADDIE model was followed, which guided each stage of media development: needs assessment, design, development or production of materials, installation and use, and evaluation. Data were collected through expert validation questionnaires and student practicality questionnaires. The medium scored 92% total on expert validation, with its contents, design and media elements all receiving excellent evaluations. Again, the practicality test showed a very high score of 97%, proving that students liked and found it useful in learning storytelling. They also felt the media helped them to understand the proper procedures greatly; most of them were able to tell their own stories after some guidance from training programs supported through use of this technology. These findings are consistent with previous studies that indicate Google Sites are very well received by users at an institute. The results offer new evidence of the usefulness and applicability to oral storytelling—an area heretofore underutilized within Indonesian language education. In conclusion, the Google Sites-based interactive multimedia materials developed in this investigation are very accessible and adaptable to the Merdeka Curriculum, helping nur ture creativity, communications competencies and digital know-how in primary school children.